Life Skills Development in Prevention of Smoking in Female Student by Integrative Group Counseling, Rat Pracha Nukhro School - Maimahat, Zanita (International Journal of Psychosocial Rehabilitation, 2020)
The research objectives were: 1) to study the life skills level to prevent smoking of female students. 2) to compare the life skills level to prevent smoking of female students in the experimental group receiving the integrated group counseling consisted of pre-experiment, post-experiment and follow-up phase, and 3) to compare the life skills level to prevent smoking of female students by integrative group counseling between experimental group and control group consisted of pre-experiment, post-experiment and follow-up phase. The samples were 16 students from sixth grade female students in the second semester of academic year 2017, at Rat Pracha Nukhro School. Selected through random sample simple to be experimental group 8 and control group 8. The result as follows: 1). The life skills level for preventing smoking among female students is in a low level With mean (x = 2.09) (SD = 0.81) 2). The experimental group female students who received the integrated group counseling program had life skills to prevent smoking during pre-experiment, post-experiment and follow-up phase statistically significant differences at the .05 level. 3). Life skills to prevent smoking of the female students in the experimental group receiving the integrated group counseling program is higher than female students in the control group without integrated group counseling during pre-experiment, post-experiment and follow-up phase statistically significant differences at the .01 level.